## Forum Replies Created

Viewing 10 posts - 1 through 10 (of 10 total)
• Author
Posts
• in reply to: Which equation has x = -6 as the solution? #10392
nazrina
Participant

Explanation:
For option (d)
log with base 3 (-2x-3) = 2
=> -2x – 3 = 3^2
=> -2x – 3 = 9
=> -2x = 12
=> x = -6

• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10376
nazrina
Participant

Mn(2+), Cr(6+), O(-2)

Explanation:

The typical oxidation state of oxygen is -2. Manganese typically takes a +2 oxidation state. This leaves chromium to balance the oxidation state(the oxidation states must sum to zero in a neutral compound).

Thus, 2 – 8 + Cr = 0

We have Cr(6+) which is its maximum oxidation number.

• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10317
nazrina
Participant

Slope of a line, m = (y2-y1/x2-x1)
=> m = ( (0-3)/(5-1) )
=> m = -3/4

∴ the correct option is (b)

• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10357
nazrina
Participant

Given: a(x) = 3x+1 , b(x) = (x-4)^1/2

(b o a)(x) = b(a(x))
= b(3x+1)
= ((3x+1)-4)^1/2
= (3x-3)^1/2
= 3(x-1)^1/2

So, the domain of x should be greater than equal to 1
i.e. x belongs to (1,infinity)

Therefore the correct answer is (c).

• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10370
nazrina
Participant

The equations that shows Mn^3+ acts as an acid are

1. [Mn(H2O)6]^+3 + H2O —-> [MnOH(H2O)5]^+2 + H3O^+
2. Mn^3+(aq) + H2O(l) ⇌ Mn(OH)^2+(aq) + H^+(aq)
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10387
nazrina
Participant

Electron microscopes have two key advantages when compared to light microscopes:

1. They have a much higher range of magnification (can detect smaller structures).
2. They have a much higher resolution (can provide clearer and more detailed images).
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#10407
nazrina
Participant

Equation of a line
=> y – y1 = m(x-x1)
=> y-1/3 = 3/4(x-4)

Therefore the correct option is (b) y-1/3 = 3/4(x-4)

• This reply was modified 2 years, 11 months ago by ProtonsTalk.
• This reply was modified 2 years, 11 months ago by ProtonsTalk.
#9911
nazrina
Participant

Given:
f(x) = 3x² + 1
g(x) = 1 – x

To find:
(f – g)(2)

Solution:
(f-g)(x) = f(x)-g(x)
(f-g)(x) = (3x² + 1)-(1-x)
(f-g)(x) = 3x²+x
(f-g)(2) = 3(2)² + 2
(f-g)(2) = 12+2
(f-g)(2) = 14

Therefore the correct option is (b)

#9995
nazrina
Participant

The correct option is (A)

Explanation:

If a^2 + b^2 = c^2 ,then triangle will be right angled.
If a^2 + b^2 > c^2 ,then theta will be acute.
If a^2 + b^2 < c^2 ,then theta will be obtuse.

Here,10^2 + 12^2 =244 > 15^2
Therefore, option (A) will be correct

#10210
nazrina
Participant